Representasi Perempuan Abad 21 Dalam Novel Jalan Panjang Menuju Pulang Karya Pipiet Senja Kajian: Feminisme Eksistensialis - Irsa Fitriani; Paul Diman; Indra Perdana; Misnawati Misnawati; Jumadi Jumadi (Universitas Palan, 2023)
The purpose of this study is to describe the characters and characterizations, as well as to describe the representation of the existence of 21st century women in the main character in the novel Jalan Panjang Menuju Pulang by Pipiet Senja. This research is a qualitative descriptive study using the documentation method. Data analysis techniques used reading techniques and note-taking techniques, then the results of data analysis were presented in descriptive form. The theory used in this study is Simone de Beauvoir's existentialist feminist theory. The source of the data in this study was a novel entitled The Long Way to Go Home by Pipiet Senja. The total data findings in this study found 95 data, namely 40 data from characters and characterizations and 55 data from the representation of 21st century women in the novel Jalan Panjang Menuju Pulang by Pipiet Senja. The results of the analysis of the novel Jalan Panjang Toward Home by Pipiet Senja can be concluded that the main female character, Fatin, can realize her existence from the oppression she has experienced. The results showed that the forms of oppression experienced by Fatin's character were verbal violence (5 data), non-verbal violence (18 data), and sexual harassment (7 data). Fatin's character experienced verbal and non-verbal violence due to the actions of Rimbong who was her husband and also her new boyfriend Frankie whom she met in the Netherlands, while Fatin experienced sexual harassment due to the actions of Hans, a white man who stayed at the Tiara Hotel where Fatin worked, and was also carried out by Frankie . The representation which implies meaning and ideology as a symbol of the 21st century women's struggle against oppression as a form of existence, is carried out by the character Fatin. As for the form of the Fatin character's struggle against oppression as a form of her existence, namely by daring to fight (12 data), trying to rise from oppression (9 data), and working (4 data).